Analysis of Active Labour Market Measures within National Employment Services (NES) in Albania: The case of NES Tirana - Dhembo, Elona (Ревија за социјална политика/Journal of Social Policy, 2014)
Despite its economic growth in the past decades, Albania continues to show high unemployment rates, particularly in women and youth, as demonstrated in the yearly reports of the Albanian Institute of Statistics. Promoting women and youth participation in labour market is of utmost importance forAlbania. The Sectoral Strategy on Employment 2007-2013 focuses on strengthening the capacity of the National Employment Service (NES) to administer active and passive labour market programmes. A main priority of the labour market policy reform is to reorient NES towards provision of services– planning, designing, monitoring and evaluating active labour market policies (ALMPs) targeting groups at risk of labour market exclusion. This paper aims to show how targeted beneficiaries of ALMPs in Albania, particularly women and youth are reached and their needs addressed by these policies, by looking at the case of NES regional office in Tirana (the capital, covering almost1/3 of Albanian population).A combination of secondary quantitative data and primary qualitative data are used to map the current state of the service and its dynamics, challenges and opportunities. The paper finds evidence of gender-blind approaches, limited policy power at regional level, poor evidence-based policymaking, insufficient training/qualification programs, and limited follow-up leading at NES services not being considered as a main job seeking strategy for groups it targets.